Gambaran Konflik pada Keluarga dengan Lansia - Ansar, Wilda; Wahyuni, Sri; Putri, Nur Mazaya; Supiyanti, Nur Anindi (SOCIETIES: Journal of Social Sciences and Humanities, 2024)
Abstract. Family conflicts with the elderly are a significant issue that requires attention. This research aims to provide a picture of the conflicts that commonly occur in families with the elderly. A search for relevant articles was conducted using the keywords: